Augmentation of communicative skills among rural high school students in India - Boobalan, Rathika; Loganathan, Saranraj; Gyamfi, Abraham (Frontiers in Education, 2024)
Introduction This study aims to focus on government school students, who struggle hard to express themselves in English. Methods A two-group simple randomized design was used for this study, and an experimental study was carried out among 60 rural high school students. ‘Captivating activities’ (listening, speaking, reading, and writing) have been used to find the effect on learners’ communication skills. Furthermore, a pre-test and a post-test were conducted between groups, and their scores were analyzed. A paired sample t-test was carried out to identify the difference between controlled and experimental groups. Results The results showed that there was a significant average difference observed between the pre-test and post-test scores (t28 = 8.327, p = 0.000, p < 0.01) of the experimental group. Discussion As an outcome of the tested strategy, it was understood that an English-speaking environment can help students improve their language skills to some extent. It was concluded that the captivating activities (listening, speaking, reading, and writing) are effective for augmenting learners’ communication skills.